Calorimetric determination of the enthalpy change for the alpha-helix to coil transition of an alanine peptide in water. - Scholtz, J M (1991)
The enthalpy change (delta H) accompanying the alpha-helix to random coil transition in water has been determined calorimetrically for a 50-residue peptide of defined sequence that contains primarily alanine. The enthalpy of helix formation is one of the basic parameters needed to predict thermal unfolding curves for peptide helices and it provides a starting point for analysis of the peptide hydrogen bond. The experimental uncertainty in delta H reflects the fact that the transition curve is too broad to measure in its entirety, which precludes fitting the baselines directly. A lower limit for delta H of unfolding, 0.9 kcal/mol per residue, is given by assuming that the change in heat capacity (delta Cp) is zero, and allowing the baseline to intersect the transition curve at the lowest measured Cp value. Use of the van't Hoff equation plus least-squares fitting to determine a more probable baseline gives delta H = 1.3 kcal/mol per residue. Earlier studies of poly(L-lysine) and poly(L-glutamate) have given 1.1 kcal/mol per residue. Those investigations, along with our present result, suggest that the side chain has little effect on delta H. The possibility that the peptide hydrogen bond shows a correspondingly large delta H, and the implications for protein stability, are discussed.